Impact of COVID-19 on diagnosis of primary pulmonary coccidioidomycosis. Issue 35 (2nd September 2022) - Ashcherkin, Nikita; Gupta, Simran; Huff, Daniel A.; Vikram, Holenarasipur R; Ampel, Neil M.; Fischer, Karen M.; Blair, Janis E.
Abstract : The COVID-19 pandemic has disrupted medical care worldwide and caused delays in care for many illnesses and procedures unrelated to COVID-19; however, less clear is how it may have affected diagnosis of conditions that present with similar symptoms, such as primary pulmonary coccidioidomycosis (PPC). We conducted an observational cohort study of patients diagnosed with PPC between March 1 and December 1 in 2 years: 2019 (before COVID-19) and in 2020 (after COVID-19) to compare the time from symptom onset to PPC diagnosis. Relevant demographic and clinical variables were collected, and statistical analyses were performed with the χ 2 test, Wilcoxon rank sum test, and Cox proportional hazards regression analysis. During 2019, 83 patients were diagnosed with PPC. During 2020, 113 patients were diagnosed with PPC. For both groups, the median time from symptom onset to diagnosis of PPC was 14 days ( P = .13). No significant differences in time to diagnosis existed between the 2 years for location of diagnosis (outpatient clinic, emergency department, or in hospital), for computed tomographic imaging performed before diagnosis, or for number of COVID-19 tests received before PPC diagnosis. In addition, there were no differences in the 2 years between the total number of clinical visits before diagnosis. However, patients in the post-COVID-19 group who had fever were diagnosed with PPC earlier than those without fever (hazard ratio, 1.77; 95% confidence interval, 1.15–2.73; P = .01). Contrary to what we expected, no significant delay in diagnosis of PPC occurred during the COVID-19 pandemic.